Crab Abon Fishery Product as a Preference of Consumption Side Dish and Its Business Opportunities in Balikpapan City, Indonesia - Haqiqansyah, Gusti; Abdusysyahid, Said; Boa, Handayani (GHMJ (Global Health Management Journal), 2025)
Background: Diversification of processed fishery products to increase the added value of fishery products, including processed crab abon products. As well as, the product is kindly alternative consumption side dishes. Crab abon is a fishery product that is developing and becoming a superior snack product typical of Balikpapan city. Thus, the benefits and feasibility of the business are quite promising in the future. Aims: The study aims (1) to identify the crab abon consumption of costumers, and (2) to analysis the profitability of the crab abon business in Manggar Baru Village. Methods: The research was conducted from August to November 2024, in Manggar Baru, Balikpapan city. Data was collected through survey methods and in depth-interviews with business actors. Then the data was analysed using the business efficiency analysis approach, Net Profit Margin (NPM), and Return on Investment (ROI). Results: The results of the study showed that costumers bought crab abon as the preference of consumption side dishes, where the average production of crab abon in a month was around 90 kg which packaged in a size of 50 grams per pack by the crab abon business. The crab abon processing business was efficient and feasible with an RCR value of 1.60, and an NPM value of 37.58%, meaning that for every IDR. 1,000,000 from the crab abon sales turnover, it was able to generate a net profit of IDR. 375,800, while the ROI value was 20.75%, which means that every IDR. 1,000,000 investment capitals will provide a net profit of IDR. 207,500. Conclusion: The average production of crab abon (Bonting Snack Kepiting) in a month was around 90 kg to meet consumption side dishes of costumers. Crab abon business is profitable that every IDR.1,000,000 investment capitals will provide a net profit of IDR. 207,500. The value of crab abon business is efficient, feasible and profitable, as well as having wide chance in the future. To support the residents through more measurable programs for the increase of fish consumption, crab abon can be alternative consumed product. Received: 09 January 2025 | Reviewed: 19 January 2025 | Revised: 27 January 2025 | Accepted: 13 February 2025. Dimension Badge: